Assessment of cardiac function, blood flow and myocardial tissue relaxation parameters at 0.35 T. (4th May 2020) - Varghese, Juliet; Craft, Jason; Crabtree, Christopher D.; Liu, Yingmin; Jin, Ning; Chow, Kelvin; Ahmad, Rizwan; Simonetti, Orlando P.
Abstract : A low field strength (B0) system could increase cardiac MRI availability for patients otherwise contraindicated at higher field. Lower equipment costs could also broaden cardiac MR accessibility. The current study investigated the feasibility of cardiac function with steady‐state free precession and flow assessment with phase contrast (PC) cine images at 0.35 T, and evaluated differences in myocardial relaxation times using quantitative T1, T2 and T2* maps by comparison with 1.5 and 3 T results in a small cohort of six healthy volunteers. Signal‐to‐noise ratio (SNR) differences across systems were characterized with proton density‐weighted spin echo phantom data. SNR at 0.35 T was lower by factors of 5.5 and 15.0 compared with the 1.5 and 3 T systems used in this study. All cine images at 0.35 T scored 3 or greater on a five‐point image quality scale. Normalized blood‐myocardium contrast in cine images, left ventricular volumes (end diastolic volume, end systolic volume) and function (ejection fraction and stroke volume) measures at 0.35 T matched 1.5 and 3 T results. Phase‐to‐noise ratio in 0.35 T PC images (11.7 ± 1.9) was lower than 1.5 T (18.7 ± 5.2) and 3 T (44.9 ± 16.5). Peak velocity and stroke volume determined from PC images were similar across systems. Myocardial T1 increased (564 ± 13 ms at 0.35 T, 955 ± 19 ms at 1.5 T and 1200 ± 35 ms at 3 T) while T2 (59 ± 4 ms at 0.35 T, 49 ± 3 ms at 1.5 T and 40 ± 2 ms at 3 T) and T2* (42 ± 8 ms at 0.35 T, 33 ± 6 ms at 1.5 T and 24 ± 3 ms at 3 T) decreased with increasing B0. Despite SNR deficits, cardiovascular function, flow assessment and myocardial relaxation parameter mapping is feasible at 0.35 T using standard cardiovascular imaging sequences. Abstract : This work demonstrates the feasibility of cardiovascular function and flow assessment, and myocardial relaxation parameter mapping at a 0.35 T low‐field strength system. Inherently lower SNR does not impact quantitative analysis at 0.35 T as results are comparable with clinical 1.5 and 3 T systems. Reduced myocardial T1 and longer T2/T2* at 0.35 T may offset SNR deficits in certain cardiac MR applications. Our results thus support the potential for low‐field MRI to expand cardiac MR availability and accessibility.